SARANA BAHASA MATEMATIKA STATISTIK DALAM PENDEKATAN DESKRIPTIF UNTUK BERPIKIR SECARA ILMIAH - Johar Amir; Irwan Soulisa (SOSCIED, 2023)
The aim of the research is to find out the means of language, mathematics, statistics in thinking scientifically. Formulation of the problem: how to use language, mathematics, statistics in thinking scientifically? The method used in this research is a qualitative method with a descriptive approach, the way to obtain data is in the form of a literature study. The results of this study are that the stages of scientific activity require tools in the form of scientific thinking facilities. The means of scientific thinking function only as tools for humans to think scientifically in order to gain knowledge. Language is a means of communicating systematic ways of thinking in acquiring knowledge. Mathematics is a means of deductive thinking, so people can use statistics to think inductively. Deductive thinking and inductive thinking are needed to support correct scientific activities so that they will produce correct knowledge. Meanwhile, statistics should not be underestimated by people who want to be able to carry out scientific activities well. Mastery of statistics is very necessary for people who will draw valid conclusions. Statistics must be seen as equal to mathematics.